2013
DOI: 10.1007/s11244-013-0071-9
|View full text |Cite
|
Sign up to set email alerts
|

Near Surface Phase Transition of Solute Derived Pt Monolayers

Abstract: As the loadings of precious metals in surfacechemical systems continue to decrease for photo-and electro-catalysts for energy and environmental applications, the study of near-surface electronic and atomic structure in functional materials becomes critically important. Extremely small quantities of active elements, whether grown as clusters or ultrathin films, exhibit changes in catalytic activity that arise from both size effects and electron-transfer effects. These size and transfer effects can be related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…We further observe the opposing chemical shifts in the Au and Pt 4f 7/2 peak from 2 to 3 nominal multilayers of Pt, indicating that net charge transfer between the substrate and the surface atoms (ligand effect) is dimensionally tunable. Systematic studies of the dimensional tuning of charge transfer to/from Pt monolayer films can be found elsewhere for the graphene‐less and the with‐graphene cases . These studies showed that subtle core‐level shifts are correlated to the shifts in the observed ORR potentials.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…We further observe the opposing chemical shifts in the Au and Pt 4f 7/2 peak from 2 to 3 nominal multilayers of Pt, indicating that net charge transfer between the substrate and the surface atoms (ligand effect) is dimensionally tunable. Systematic studies of the dimensional tuning of charge transfer to/from Pt monolayer films can be found elsewhere for the graphene‐less and the with‐graphene cases . These studies showed that subtle core‐level shifts are correlated to the shifts in the observed ORR potentials.…”
Section: Resultsmentioning
confidence: 96%
“…Pt and graphene architectures were prepared using chemical vapor deposition and the surface limited redox replacement (SLRR) as per procedures detailed in Supporting Information—Synthesis, while SLRR and its variant, electrochemical atomic layer deposition, have been used in the past to deposit metal on metal by Stickney et al, Brankovic et al, Fayette et al, Alamgir et al has successfully used it to produce uniform ultrathin platinum layers over various substrates, including bulk metals like gold and ruthenium, oxides such as TiO 2 and 2D materials like graphene . Extended X‐ray absortion fine structure (EXAFS) was conducted on Pt_nML/GR/Ligand samples at the National Synchrotron Light Source (NSLS Beamline X23A2) and analysis was performed to investigate the Pt atomic near‐neighbor structure ( Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…160,182 For Pt adsorption on Au, changes in DDEC NACs as a function of Pt coverage were correlated to XPS and XAS data. 183 Although the extraction of NACs from diffraction experiments is challenging, 179 some of the most careful diffraction studies on crystals with small unit cells (e.g., formamide, MgO, and NaF) gave NACs similar to the DDEC method. 160 The DDEC method also includes a way to compute atomic spin moments (ASMs) in materials with collinear and noncollinear magnetism.…”
Section: Spatial Information On 3d-supported Catalystsmentioning
confidence: 99%